TANTANGAN DAN KENDALA PELAKSANAAN PENDIDIKAN PANCASILA DALAM KURIKULUM 2013 DAN KURIKULUM MERDEKA - Tina Septiana; Muhammad Tantan; M. Akbar Maulana Irfan; Dani Fajar Purnama; Muhammad Samhan; Feri Susanto Sopian (Educatus, 2025)
Pancasila education plays a strategic role in shaping national character and instilling the values of nationalism in students. However, its implementation often encounters various challenges in both the 2013 Curriculum and the Independent Curriculum. This study aims to analyze the challenges and obstacles in the implementation of Pancasila education within these two curricula in order to provide recommendations for educational policy improvement. The research employs a qualitative approach using a literature study method that examines various scholarly sources related to curriculum development and implementation. The findings indicate that the development of the Pancasila education curriculum has raised public concerns due to the lack of involvement of experts, academics, stakeholders, and teacher professional associations, as well as the absence of a comprehensive evaluation of the previous curriculum. In the 2013 Curriculum, the identified challenges include limited learning resources, minimal time allocation, and an imbalance in the development of attitudes, knowledge, and skills competencies. Meanwhile, in the Independent Curriculum, obstacles arise from the unclear boundaries of the independent learning concept, inadequate facilities and infrastructure, and an unstructured distribution of learning outcomes. These findings imply the need for curriculum policy improvements, increased stakeholder involvement, and adequate resource support so that Pancasila education can be implemented optimally and remain relevant to students’ needs in the global era.